Meso curriculum to improve the english teaching learning process of the sixth year of basic education at leonardo moscoso moreno school located in isinche grande neighborhood - pujili city during the academic cycle april – august 2014 - Guamán Flores, María Fernanda (2015)
Nowadays, to learn English language has become a challenge in the field of education due to the multiple shortcomings that exist in the teaching learning process of this language. Both teachers and students do not have a guide for the English teaching learning process. It has caused in students a shortcoming in the production of English language. Thus, the vocabulary is limited and the total unawareness of grammatical structures. This is due to the lack of systematization with contents and methodology. From this perspective, the present research work had as a purpose to provide teacher with an updated Meso Curriculum containing methods, contents, and techniques of evaluation in a systematic way, based on reality and student´s needs in order to help their inter-learning. The methodology used in the research work was the descriptive method with the objective to collect suitable theoretical foundations. Surveys and interview were applied to teachers and the Director of the institution in order to know shortcomings and requirements for the development of the proposal....